Crop Residue Management Strategies to Reduce Nitrogen Losses during the Winter Leaching Period after Autumn Spinach Harvest - Christian Frerichs; Stephan Glied-Olsen; Stefaan De Neve; Gabriele Broll; Diemo Daum (Agronomy, 2022)
In open-field vegetable production, high quantities of soil mineral nitrogen (Nmin) and N-rich crop residues often remain in the field at harvest. After the harvest of crops in autumn, this N can lead to considerable nitrate (NO3−) losses during the subsequent winter leaching period. In four field trials, different tillage depths (3–4, 10, 30 cm) and dates (early autumn, late autumn, early spring) were investigated to reduce N losses after growing spinach in the autumn. In a further treatment, the nitrification inhibitor 3,4-Dimethylpyrazole phosphate (DMPP) was directly applied to the crop residues. Potential N losses were calculated by a balance sheet approach based on Nmin concentration (0–90 cm), measured N mineralization and N uptake by catch crops. By postponing the tillage date from early to late autumn or spring, resprouting spinach stubbles acted as a catch crop, reducing N losses by up to 61 kg ha−1. However, if the spinach biomass collapsed, the N losses increased by up to 33 kg ha−1 even without tillage. The application of DMPP as well as the tillage depth were less effective. Overall, postponing tillage to spring seems to be the most promising approach for reducing N losses during the off-season.